The Beneficial Aspects of Implementing Ifrad Pilgrimage for Indonesian Pilgrims - Sokon Saragih; Asmuni Asmuni; Dhiauddin Tanjung (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Ifrad pilgrimage is a form of Hajj where an individual intends only for Hajj upon entering the state of Ihram. The pilgrim declares Labbaik Bahaj and performs Tawaf Qudum after entering Mecca, remaining in the state of Ihram until the designated Hajj period. Subsequently, the pilgrim follows all the Hajj rituals, including the standing at Arafah, staying at Muzdalifah, casting stones at Jamarat Al-Aqabah, performing Tawaf Ifadhah, Sa'i between Safa and Marwa, and spending the night at Mina for stone throwing on the days of Tashriq. After completing all the Hajj rituals, the pilgrim performs the second Tahallul, exits Mecca, and begins the second Ihram with the intention of Umrah if planning to undertake Umrah rituals. Tamattu' pilgrimage involves initially intending to perform Umrah upon entering the Miqat by saying Labbaik in Umrah. Upon entering Mecca, the pilgrim completes all Umrah rituals such as Tawaf and Sa'i, then shaves or trims the hair, concluding the state of Ihram. On the 8th of Dhu al-Hijjah, the pilgrim enters into the Hajj Ihram, performs Hajj rituals like standing at Arafah, Tawaf, Sa'i, and others comprehensively. Qiran pilgrimage is when an individual intends to perform both Hajj and Umrah simultaneously upon entering Ihram by uttering specific words. The individual remains in the state of Ihram until completing the Hajj rituals. During the Hajj, there is no need for additional Tawaf and Sa'i for Umrah; performing the Tawaf and Sa'i for Hajj is sufficient. Among these three types of pilgrimage, the Ifrad model is considered the least burdensome for pilgrims. This model does not incur penalties, and the greater benefit in performing the Hajj pilgrimage is achieved through the Ifrad model.